2022
DOI: 10.3346/jkms.2022.37.e272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cancer-Related Dysfunctional Beliefs About Sleep on Fear of Cancer Progression in the Coronavirus Pandemic

Abstract: Background This study aimed to explore clinical correlates of fear of progression (FoP) among patients with cancer during the coronavirus disease 2019 (COVID-19) pandemic and examine the mediation effect of cancer-related dysfunctional beliefs about sleep (C-DBS). Methods Medical charts of patients with cancer who visited a psycho-oncology clinic between July and November 2021 were reviewed. Baseline socio-demographic and cancer-related variables were collected. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 57 publications
(55 reference statements)
4
32
0
Order By: Relevance
“…In our previous study, we observed a clue for the relationship between viral anxiety and dysfunctional beliefs about sleep [30]. Among cancer patients, cancer-related dysfunctional beliefs about sleep mediated the association between viral anxiety and fear of progression [30]. And also, we observed that the effects of viral anxiety on functional impairment of cancer patients were mediated by cancer-related dysfunctional beliefs about sleep [13].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our previous study, we observed a clue for the relationship between viral anxiety and dysfunctional beliefs about sleep [30]. Among cancer patients, cancer-related dysfunctional beliefs about sleep mediated the association between viral anxiety and fear of progression [30]. And also, we observed that the effects of viral anxiety on functional impairment of cancer patients were mediated by cancer-related dysfunctional beliefs about sleep [13].…”
Section: Discussionmentioning
confidence: 72%
“…We also hypothesized that viral anxiety will at least partially mediate the influence of dysfunctional beliefs about sleep on insomnia severity. In our previous study, we observed a clue for the relationship between viral anxiety and dysfunctional beliefs about sleep [30]. Among cancer patients, cancer-related dysfunctional beliefs about sleep mediated the association between viral anxiety and fear of progression [30].…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that patients with cancer have difficulties in initiating or maintaining sleep, wake up earlier than expected, and are unable to fall back to sleep; furthermore, they experience excessive daytime sleepiness and other sleep disorders, which remain as well during the recovery period[ 10 ]. Studies have shown that the stronger the fear of recurrence in patients with cancer, the worse their sleep quality[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can exaggerate the negative effects of sleep deprivation and magnify the impact of sleep deprivation on the prognosis of the disease. False beliefs about sleep make cancer insomniacs more prone to thoughts that are so bad that they often hold beliefs such as insomnia may cause long-term negative consequences, which play a prominent role in insomnia's prolongation [30]. Many studies have reported that false sleep beliefs are associated with the occurrence and maintenance of sleep disorders in cancer patients [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…They perceive this matter as a matter of life and death. In this particular scenario, cancer patients often develop erroneous beliefs regarding the crucial role of sleep at speci c times in maintaining immune function, as well as the serious detrimental impact of poor sleep on cancer progression[30,49,50]. The two new items in the C-DBAS-14 do a good job of covering false beliefs about sleep that are unique to cancer patients and are an effective tool for assessing sleep beliefs and attitudes in cancer patients.The results show that the Chinese version of C-DBAS-14 has the appropriate reliability and validity to evaluate incorrect beliefs about sleep in cancer patients.…”
mentioning
confidence: 99%